E-HEALTH LITERACY AMONG STUDENTS - Gazibara, Tatjana; Cakic, Jelena; Cakic, Milica; Zejnelagic, Redzeb; Popovic, Aleksandra; Grgurevic, Anita (Medical Research, 2022)
Introduction/Aim: There is a lack of data on eHealth literacy and potential differences ineHealth literacy among university students. The aim of this study was to evaluate potentialdifferences in eHealth literacy between students of sports and medicine.Material and Methods: From April to October 2017, we conducted a cross-sectional study at theFaculty of Sports and Physical Education and the Faculty of Medicine, University of Belgrade,Serbia,. A total of 89 sports students and 301 medical students were included. The eHealthLiteracy Scale (eHEALS) was applied to evaluate eHealth literacy.Results: Compared with sports students, medical students had higher median eHEALS score (27vs. 30, respectively, P=0.008). Also, medical students were two times more confident than sportsstudents in where to locate helpful online health resources and how to use online healthinformation. We did not obtain a significant hierarchical linear regression model for factorscontributing to better eHealth literacy among sports students. In medical students, we observedthat being female, residing outside of the capital city before studying at the University, youngerage at first Internet use, use of health-related websites and smartphone apps as well as less stronginfluence of online health-related information on decision making was associated with better self-perceived eHealth literacy.Conclusion: Medical students perceived their eHealth literacy skills as more confident comparedto sports students. Factors influencing better eHealth literacy seem to depend on their fields ofstudy
Keywords: electronic health literacy; students; medicine; sport; physical education